(untitled) (Indian Journal of Public Health Research & Development, 2020)
Aim : The objective of this study was to evaluate the knowledge, attitude and practice of dentists towards provision of dental care to pregnant women. Material and Method: A multiple choice questionnaire was self-administered to dentists in Chennai. The collected data was statistically analysed. Results: Although majority of the dentists were well informed about the management of pregnant patients, dilemmatic attitudes were seen regarding dental radiographs, local anaesthesia and prenatal fluoride supplementation. Conclusion: This demonstrates the need to broaden the knowledge of dental surgeons via CDE programs and workshops.